Techniques and Experimental Results for Performance Analysis of Photovoltaic Modules Installed in Buildings. (March 2017) - Spertino, F.; Ahmad, J.; Ciocia, A.; Di Leo, P.
Abstract: Photovotaic (PV) modules applied to buildings form a unique surface at the same roof inclination, replacing the tiles. Such PV systems are affected by thermal and mechanical stresses, and remarkable dirt. Another issue is the partial shading with possible failure of bypass diodes. In this paper a sample of PV modules, affected by the previous issues, was tested by electroluminescence and I-V curve scanning, to quantify power losses according to the causes. The experimental results are presented, demonstrating that the most important causes of losses are the cracks in module's solar cells and the failure of their bypass diodes.